Bioprospecting of Kerangas Forest as Natural Medicine Material Sources: Screening Phytochemistry Compound of Kerangas Forest Tree Species - Kissinger Kissinger; Ahmad Yamani; Gusti AR Thamrin; Rina Muhayyah (Journal of Wetlands Environmental Management, 2016)
Bioprospecting is an effort to create a value for biodiversity. Bioactivity identification of tree species is an important step to get high economic value from kerangas forest. Screening bioactivity of plants was conducted by ethnobotanical survey and qualitative phytochemistry compound tests. Dried leaves and barks of selected trees from kerangas forest were tested for qualitative phythochemistry compound. Result showed that parts of selected trees from kerangas forest had various phythochemistry compounds. Methanol extract of kerangas tree species have potential bioactivities. There were total of 42 plants located in heath forest, 38 species of which are used by the public as a medicine (90.48%). The number of tree species that are always available in all locations of heath forest are 10 species. There are 8 species of which are commonly used by the community as a medicine. The benefits obtained from 10 species were as analgesic, antibacterial, antidiabetic, anti-plasmodium, and vitality. One species that potentially based on the knowledge society as antidiabetic contained in heath forest is S.belangeran.Bioprospecting is an effort to create a value for biodiversity. Bioactivity identification of tree species is an important step to get high economic value from kerangas forest. Screening bioactivity of plantswas conducted by ethnobotanical[u1] survey and qualitative phytochemistry compound tests. Dried leaves and barks of selected trees from kerangas forest were tested for qualitative phythochemistry compound. Result showed that parts of selected trees from kerangas forest had various phythochemistry compounds. It can be concluded that methanol extract of kerangas tree species have potential bioactivities.[u2]  [u1]spacing [u2]for what, more detail